Establishing Test Procedures for Determining Precipitate Sedimentation Rates at Varying Temperatures - Iboroma, Daopuye Soye (Faculty of Natural and Applied Sciences Journal of Applied and Physical Sciences, 2025)
A laboratory setup and test procedure for determining precipitate sedimentation rate at varying temperatures are presented. The objective is to improve on conventional sedimentation study apparatus as well as generate reproducible sedimentation data under controlled thermal conditions. The setup comprises a transparent graduated cylindrical tube for sedimentation, a transparent water bath for heat transmission, a magnetic stirrer for uniform heat distribution, a temperature-controlled heating mantle for heat generation, a thermometer and a digital stop watch for timing. The procedure involves monitoring gravitational sedimentation of precipitate formed in a reaction medium over time. The setup has been applied to study the influence of temperature on the sedimentation profiles of aluminium and iron (II) phosphate precipitate suspensions. The setup is suitable for quantifying sedimentation rates of insoluble inorganic compounds and assessing the physical stability of pharmaceutical suspensions.